0.5(x+2)-(3x+8)=1.6(x-2)+9

Simple and best practice solution for 0.5(x+2)-(3x+8)=1.6(x-2)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(x+2)-(3x+8)=1.6(x-2)+9 equation:


Simplifying
0.5(x + 2) + -1(3x + 8) = 1.6(x + -2) + 9

Reorder the terms:
0.5(2 + x) + -1(3x + 8) = 1.6(x + -2) + 9
(2 * 0.5 + x * 0.5) + -1(3x + 8) = 1.6(x + -2) + 9
(1 + 0.5x) + -1(3x + 8) = 1.6(x + -2) + 9

Reorder the terms:
1 + 0.5x + -1(8 + 3x) = 1.6(x + -2) + 9
1 + 0.5x + (8 * -1 + 3x * -1) = 1.6(x + -2) + 9
1 + 0.5x + (-8 + -3x) = 1.6(x + -2) + 9

Reorder the terms:
1 + -8 + 0.5x + -3x = 1.6(x + -2) + 9

Combine like terms: 1 + -8 = -7
-7 + 0.5x + -3x = 1.6(x + -2) + 9

Combine like terms: 0.5x + -3x = -2.5x
-7 + -2.5x = 1.6(x + -2) + 9

Reorder the terms:
-7 + -2.5x = 1.6(-2 + x) + 9
-7 + -2.5x = (-2 * 1.6 + x * 1.6) + 9
-7 + -2.5x = (-3.2 + 1.6x) + 9

Reorder the terms:
-7 + -2.5x = -3.2 + 9 + 1.6x

Combine like terms: -3.2 + 9 = 5.8
-7 + -2.5x = 5.8 + 1.6x

Solving
-7 + -2.5x = 5.8 + 1.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.6x' to each side of the equation.
-7 + -2.5x + -1.6x = 5.8 + 1.6x + -1.6x

Combine like terms: -2.5x + -1.6x = -4.1x
-7 + -4.1x = 5.8 + 1.6x + -1.6x

Combine like terms: 1.6x + -1.6x = 0.0
-7 + -4.1x = 5.8 + 0.0
-7 + -4.1x = 5.8

Add '7' to each side of the equation.
-7 + 7 + -4.1x = 5.8 + 7

Combine like terms: -7 + 7 = 0
0 + -4.1x = 5.8 + 7
-4.1x = 5.8 + 7

Combine like terms: 5.8 + 7 = 12.8
-4.1x = 12.8

Divide each side by '-4.1'.
x = -3.12195122

Simplifying
x = -3.12195122

See similar equations:

| 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 | | -69=6(-3n-2)-(-5n-8) | | 19=x-32 | | A(-8)= | | 2y=x+13 | | 1+2p=16+7p |

Equations solver categories